Spatial patterns of plant litter in a tidal freshwater marsh and implications for marsh persistence. Issue 3 (26th April 2016) - Elmore, Andrew J.; Engelhardt, Katharina A. M.; Cadol, Daniel; Palinkas, Cindy M.
Abstract: The maintenance of marsh platform elevation under conditions of sea level rise is dependent on mineral sediment supply to marsh surfaces and conversion of above‐and belowground plant biomass to soil organic material. These physical and biological processes interact within the tidal zone, resulting in elevation‐dependent processes contributing to marsh accretion. Here, we explore spatial pattern in a variable related to aboveground biomass, plant litter, to reveal its role in the maintenance of marsh surfaces. Plant litter persisting through the dormant season represents the more recalcitrant portion of plant biomass, and as such has an extended period of influence on ecosystem processes. We conducted a field and remote sensing analysis of plant litter height, aboveground biomass, vertical cover, and stem density (collectively termed plant litter structure) at a tidal freshwater marsh located within the Potomac River estuary, USA. LiDAR and field observations show that plant litter structure becomes more prominent with increasing elevation. Spatial patterns in litter structure exhibit stability from year to year and correlate with patterns in soil organic matter content, revealed by measuring the loss on ignition of surface sediments. The amount of mineral material embedded within plant litter decreases with increasing elevation, representing an important tradeoff with litter structure. Therefore, at low elevations where litter structure is short and sparse, the role of plant litter is to capture sediment; at high elevations where litter structure is tall and dense, aboveground litter contributes organic matter to soil development. This organic matter contribution has the potential to eclipse that of belowground biomass as the root : shoot ratio of dominant species at high elevations is low compared to that of dominant species at low elevations. Because of these tradeoffs in mineral and organic matter incorporation into soil across elevation gradients, the rate of marsh surface elevation change is remarkably consistent across elevation. Because of the role of plant litter in marsh ecosystem processes, monitoring and assessment of these dynamic geomorphic marsh landscapes might be streamlined through the measurement of plant litter structure, either via LiDAR technologies or field observation.